Protection of the environment and natural resources in the new constitution of Peru - Bartra Abensur, Valentín (2002)
The environment provides the necessary for human life , flora and fauna environment. Natural resources, national heritage , are the material elements necessary to meet our requirements of food, clothing , housing , energy and other products of the current Peruvian population but also must ensure the welfare of future generations . We are borrowing today that belongs to the youth and children who will be born in Peru also have to be necessary for their welfare. The purpose of the state is to provide the common good , ie the General Welfare. Because their primary duty is to protect the environment, essential life environment and natural resources that meet the vital needs of all the inhabitants of Peru . In Peru has enshrined the protection of the environment from the highest level of the legal system to include its regulation in the political cards explicitly , so we checked in the Constitution of 1979, 1993 and Articles recently approved reform the Constitution. This stream of environmental protection at the highest legal level can also be seen in a brief review of comparative legislation of several contemporary constitutions.